Analysis of Social Marketing Intervention in the "Local Quality" Campaign - Kovačič, Špela; Ašanin Gole, Pedja (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Social marketing is today been used, more than ever for the promotion of socially desirable behavior. Moreover, to change social unwanted behavior to desired. Low level of self-sufficiency in Slovenia represents a socially undesirable behavior that is been changed by the Ministry of Agriculture, Forestry and Food, through the public campaign "Lokalna kakovost" (Local quality). The authors analyzed the use of social marketing on the case of the public campaign "Lokalna kakovost" (Local quality) and its effectiveness and efficiency checked on a sample of consumers, and compared it with the analysis of related models for the purposes of commercial marketing in retail chains.
Keywords: social marketing; self-sufficiency; Slovenia; consumption; locally produced food; origin